Hepatocellular Carcinoma with Bile Duct Thrombosis - A Case Report - Kubota, Masaru; Hashimoto, Yasuji; Imamura, Hiroki; Yagi, Yuriko; Noma, Takashi; Mokutani, Yukako; Nagai, Kenichi; Hirose, Hajime; Ide, Yoshihito; Matsuyama, Jin; Fukushima, Yukio; Nishioka, Yousuke; et al. (Gan to kagaku ryoho, 2018)
Hepatocellular carcinoma(HCC)is not commonly observed with bile duct thrombosis.Here, we report a case of HCC with bile thrombi that extended to the liver hilum.The patient was a 61-year-old man who visited us due to untreated type B hepatitis.He underwent screening with a CT scan that revealed LDA on the right posterior lobe of his liver with infiltration of the bile duct.Generally, bile resection and reconstruction should be considered for curative resection for bile thrombi; however, we attempted to conserve the common bile duct to preserve the options of percutaneous therapy in case of tumor recurrence.We performed right lobectomy of the liver.The bile duct thrombus was extracted without bile duct resection or reconstruction.The patient is alive 6 months after the surgery without any development.